2001
DOI: 10.1007/bf02345370
|View full text |Cite
|
Sign up to set email alerts
|

Application of empirical mode decomposition to heart rate variability analysis

Abstract: The analysis of heart rate variability, involving changes in the autonomic modulation conditions, demands specific capabilities not provided by either parametric or non-parametric spectral estimation methods. Moreover, these methods produce time-averaged power estimates over the entire length of the record. Recently, empirical mode decomposition and the associated Hilbert spectra have been proposed for non-linear and non-stationary time series. The application of these techniques to real and simulated short-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(111 citation statements)
references
References 23 publications
1
107
1
2
Order By: Relevance
“…Various studies (Echeverría et al 2001, Souza Neto et al 2004 can be found in the literature that have used the EMD technique for the analysis of HRV signals; however, in this study a more thorough approach has been used. In this study a new method based on CF and SDSE has been proposed for assigning the IMF components into the HF and the LF bands of the HRV signal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies (Echeverría et al 2001, Souza Neto et al 2004 can be found in the literature that have used the EMD technique for the analysis of HRV signals; however, in this study a more thorough approach has been used. In this study a new method based on CF and SDSE has been proposed for assigning the IMF components into the HF and the LF bands of the HRV signal.…”
Section: Discussionmentioning
confidence: 99%
“…In this study a new method based on CF and SDSE has been proposed for assigning the IMF components into the HF and the LF bands of the HRV signal. In previous studies (Echeverría et al 2001, Souza Neto et al 2004 the IMF components were usually split into the HF and the LF bands by manually observing their frequency contents. The results produced in this way could be quite subjective.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, each consecutive IMF had characteristically lower frequencies. It can also be observed that, although a summation of the IMFs and the residue results in the input signal, the IMFs and the residue extracted do not have the slightest propensity towards linearity, stationarity nor time-invariance (Echeverria et al, 2001;Huang and Shen, 2005;Shi and Law, 2007). This approach to signal decomposition is effectively dynamic and is void of a priori assumptions of the characteristics of the input data.…”
Section: Signal Decomposition and Noise Extractionmentioning
confidence: 99%
“…Literature references' variety reveals the extensive range of EMD applications in several areas of the biomedical engineering field. Particularly there are publications concerning the application of EMD in the study of Heart Rate Variability (HRV) [8], analysis of respiratory mechanomyographic signals [9], ECG enhancement artifact and baseline wander correction [10], R-peak detection [11], Crackle sound analysis in lung sounds [12] and enhancement of cardiotocograph signals [13]. The method is employed for filtering electromyographic (EMG) signals in order to perform attenuation of the incorporated background activity [14].…”
Section: Empirical Mode Decompositionmentioning
confidence: 99%